Informing the Strategic Rollout of Fast Electric Vehicle Charging Networks with User Charging Behaviour Data Analysis - O'Mahony, Margaret; Morrissey, Patrick (My University, 2016)
With the current range limitations of existing electric vehicle ( EV ) technology, range anxiety has been identified as one of the main barriers to their adoption. For countries or states which are predominantly rural in nature , with few major urban areas , this range limitation has the potential to be a greater barrier than in the case of large cit i es . This paper presents data recorded in Ireland on the spatial usage patterns of an existing fast charging network over an extended period. These data are used to ass ess how the infrastructure is being used cu rrently and , in particular , examines the issues relating to urban versus rural usage patterns. Existing infrastructure rollout strategies are examined in the context of the main findings from this analysis and a spatial density analysis is presented to examine how a desired density can influence a rollout strategy. It was found th at urban users have very different fast charging requirements compared to rural and commuter groups. Urban users tend to charge their vehic les close to their home as a means of extending their local EV range. EV use rs from other geographic areas tend to charge their vehicles further from their home. Bas ed on the findings of this work , it would appear that current rollout strategie s based primarily on ‘electric’ highway corridors may not be appropriate for all EV users and different infrastructure rollout strategies based on fast charging facility densities and geographic location may be more appropriate .
Procs of the 95th Annual Meeting of the Transportation Research Board, National Academy of Sciences
PUBLISHED
Washington D.C.
Keywords: Smart & Sustainable Planet; Transport